2003
DOI: 10.1002/jez.a.10242
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged response to calling songs by the L3 auditory interneuron in female crickets (Acheta domesticus): Intracellular evaluation

Abstract: The L3 auditory interneuron in female Acheta domesticus, produces two different responses to the male calling song: an immediate response and a prolonged response. The prolonged response exhibited spiking activity and a correlated prolonged depolarization, both of which are clearly seen in intracellular recordings. The morphology revealed by intracellular staining was clearly the L3 neuron. The amplitude of the prolonged depolarization associated with the prolonged response increased with increases in sound in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Intracellular recording in the integrative zone (dendrites) of the L3 neuron frequently results in increased ''spontaneous'' firing that would be difficult or impossible to distinguish from impulses created by the prolonged response. Navia et al (2003) clearly demonstrated that L3, recorded intracellularly and stained with Lucifer yellow, produced both the previously described immediate response (Atkins et al,'89) and the prolonged response. Only two pairs of neurons that arise in the prothoracic ganglion and send an axon up the cervical connective have been clearly identified and described in any of the gryllid species (L1 and L3 in A. domesticus, AN1 and AN2 in several other gryllids) that encode behaviorally important features of the CSs at carrier frequencies and intensities that are behaviorally relevant to phonotaxis.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Intracellular recording in the integrative zone (dendrites) of the L3 neuron frequently results in increased ''spontaneous'' firing that would be difficult or impossible to distinguish from impulses created by the prolonged response. Navia et al (2003) clearly demonstrated that L3, recorded intracellularly and stained with Lucifer yellow, produced both the previously described immediate response (Atkins et al,'89) and the prolonged response. Only two pairs of neurons that arise in the prothoracic ganglion and send an axon up the cervical connective have been clearly identified and described in any of the gryllid species (L1 and L3 in A. domesticus, AN1 and AN2 in several other gryllids) that encode behaviorally important features of the CSs at carrier frequencies and intensities that are behaviorally relevant to phonotaxis.…”
Section: Discussionmentioning
confidence: 83%
“…Post-stimulus time (PST) histograms and spiking rates were calculated. To avoid counting spikes of the immediate response or the reduction of the prolonged response by the delayed inhibition of L3's responses (described by Navia et al, 2003), spiking rates were determined at all intensities by measuring the last 300 ms of the interval between chirps.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations